Light-colored solar-driven PANI/polyacrylonitrile fiber with low-temperature resistance for wearable heater. (April 2023) - Ge, Fangqing; Fei, Liang; Chen, Xin; Yin, Yunjie; Wang, Chaoxia
Abstract: High-performance photothermal textiles with favorable low-temperature resistance and washing resistance demonstrate obvious superiority and growing demand. However, most photothermal conversion materials show dark color, restricting their color tunability in wearable heating garments. The light-colored solar-driven polyaniline (PANI)/polyacrylonitrile fiber with high low-temperature resistance and washing resistance is fabricated continuously via the wet-spinning method. The temperature of the solar-driven PANI/polyacrylonitrile fiber (0.5 wt%) rises from room temperature (20.00 °C) to 48.12 °C irradiated at 600 W m −2 for 10 min. Even at −30.01 °C, the equilibrium temperature of the solar-driven PANI/polyacrylonitrile fiber is maintained at 25.42 °C, demonstrating its prominent low-temperature resistance. This phenomenon is attributed to the effective and stable light absorption of PANI particles in the Vis-NIR region. The K/S value of the solar-driven PANI/polyacrylonitrile fiber is 0.08 at 700 nm, indicating the color depth is very light. Besides, the tiny temperature difference is observed after being washed 25 times, demonstrating the solar-driven PANI/polyacrylonitrile fiber possesses high washing resistance. The solar-driven PANI/polyacrylonitrile fiber can be easily woven into a bracelet or sewn into the fabric, suggesting a facile fabrication strategy overcoming the constraints of photothermal fiber color is obtained to promote the development of wearable heater. Graphical abstract: Image 1